Effects of Radiotherapy in Combination With Irinotecan and 17-AAG on Bcl-2 and Caspase 3 Gene Expression in Colorectal Cancer Cells: Radiotherapy with irinotecan and 17-AAG - Ebrahimpour, Mahnaz; Mohammadian, Mahshid; Pourheydar, Bagher; Moradi, Zhino; Behrouzkia, Zhaleh (Journal of Lasers in Medical Sciences, 2022)
Introduction: In this study, the cytotoxic and anti-cancer effects of Irinotecan as a conventional chemotherapeutic agent compared to 17-(allyl amino)-17-demethoxygeldanamycin (17-AAG) as possible radiosensitizers in the HCT-116 cell line were investigated. Methods: HCT-116 cells were treated with various concentrations of irinotecan and 17-AAG and also irradiated with a 2-Gy of X-ray radiation. Then, the cell viability was examined by a watersoluble tetrazolium-1 assay after 24 hours. For single therapies and double and triple combination cases, IC50, 0.5×IC50 and 0.25×IC50 concentrations of each drug were selected respectively for a terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) assay and other tests. In treated and untreated cells, the caspase 3 and Bcl-2 gene expression ratios were evaluated by the real-time PCR method. Likewise, caspase 3 activity was detected with a colorimetric assay. Results: In all combined treatments, including 17-AAG- radiation, irinotecan - radiation, irinotecan -17-AAG, and irinotecan-17-AAG-radiation, decreased cell viability, and increased TUNEL positive cells were presented versus the control group (P<0.05). There were increased TUNEL positive cells in the triple combination, in concentrations of 0.25×IC50 of each drug, in comparison with single and double agent treatments. Moreover, in the triple combination, the caspase 3 mRNA level and caspase 3 activity increased versus related single treatments. Likewise, in the irinotecan17-AAG-radiation combined treatment and the 17-AAG-radiation double treatment, the Bcl-2 gene expression level decreased in comparison with single therapies. Conclusion: It can be indicated that the combination of chemo-radiotherapy versus single treatments has significant anti-cancer effects. DOI:10.34172/jlms.2022.09.